Role of mitochondrial dynamics in mouse preimplantation embryonic development and its molecular mechanisms - Xiaoyan Sun; Qingyang Li; Bo Chen (Scientific Reports)
Abstract This study investigated the impact of mitochondrial dynamics on mouse preimplantation embryonic development and its underlying molecular mechanisms. Using pharmacological and genetic approaches, we demonstrated that balanced mitochondrial fusion and fission are essential for optimal embryonic development. Disruption of mitochondrial dynamics significantly impaired blastocyst formation, altered cell lineage allocation, and compromised energy metabolism. Our findings revealed that mitochondrial dynamics regulate gene expression through epigenetic modifications and influence cell survival through the modulation of apoptotic pathways. We also identified key metabolic intermediates and signaling pathways that mediate the effects of mitochondrial dynamics on embryonic development. These results provide new insights into the molecular mechanisms linking mitochondrial function to early embryonic development and suggest potential strategies for improving assisted reproductive technologies.